Association Between Serum Insulin-Like Growth Factor 1 Levels and the Clinical Symptoms of Chronic Schizophrenia: Preliminary Findings - Okamoto, Naomichi; Yoshino, Koji; Kitagawa, Shogo; Fujii, Rintaro; Hamada, Shinsuke; Ikenouchi, Atsuko; Konishi, Yuki; Ueda, Nobuhisa; Eto, Yoshinori; Tsutsumi, Yasunari; Yoshimura, Reiji (Frontiers in Psychiatry, 2021)
Purpose: The aim of this study was to investigate the relationship between serum insulin-like growth factor 1 (IGF-1) levels and the psychiatric symptoms of patients with chronic schizophrenia. We also examined the association between serum IGF-1 levels and diabetes, antipsychotic drugs, and duration of illness. Patients and methods: Patients were recruited from the University of Occupational and Environmental Health, Komine Eto Hospital, Moji Matsugae Hospital, Shin-Moji Hospital, and Tsutsumi Hospital in Kitakyushu between September 2019 and June 2020. Healthy control subjects were also recruited from the Komine Eto Hospital and University of Occupational and Environmental Health. All patients fulfilled the diagnostic criteria for schizophrenia outlined in the structured clinical interview of the Diagnostic and Statistical Manual for Mental Disorders, Fifth Edition. Patients with a history of neurological disorders, substance use, and/or other psychiatric disorders were excluded. Healthy subjects were identified as those who did not fulfil any of the criteria for diagnoses in the Diagnostic and Statistical Manual for Mental Disorders, Fifth Edition. The selection of healthy controls was based on age and sex matching of the patients as much as possible; the selected control subjects had no pre-specified medical conditions. A total of 65 patients with schizophrenia and 20 healthy subjects were included in the study. Patients with schizophrenia were assessed using the Positive and Negative Syndrome Scale (PANSS) and the Drug-Induced Extrapyramidal Symptoms Scale. Measurement of serum IGF-1 levels was based on the principle of the immunoradiometric assay. The measurements were made using antibody beads for bound/free separation. Results: Serum IGF-1 levels were significantly negatively correlated with PANSS total score (R2 = 0.06, p = 0.015) and PANSS general score (R2 = 0.088, p = 0.008), but not with PANSS positive scores and PANSS negative scores. Conclusion: The association between serum IGF-1 levels and psychiatric symptoms may be complicated in patients with chronic schizophrenia.